Smart Mobility Recent Advances, New Perspectives and Applications - Sarwat, Arif I.; Khalid, Asadullah; Hasnain Jalal, Ahmed (IntechOpen, 2023)
Smart Mobility - Recent Advances, New Perspectives and Applications explores the rapidly evolving world of connected and autonomous vehicles, providing a comprehensive look at the latest advancements and cutting-edge technologies driving this exciting industry forward. This book covers the most pressing topics in smart mobility, including sizing, sensing, simulations, safety, and cybersecurity applications, giving readers a deep understanding of the challenges and opportunities facing this emerging field. With perspectives from leading experts, the book provides insights into the future of mobility and the role that technology will play in shaping our transportation systems. Whether you are a student, engineer, or industry professional, this book offers a unique and valuable resource for those looking to stay ahead of the curve in the ever-evolving world of smart mobility and its growing impact on our daily lives.